Chemical Indicators of Cryoturbation and Microbial Processing throughout an Alaskan Permafrost Soil Depth Profile. Issue 3 (6th July 2015) - Ernakovich, Jessica G.; Wallenstein, Matthew D.; Calderón, F.J.
Abstract : Although permafrost soils contain vast stores of organic C, relatively little is known about the chemical composition of their constituent soil organic matter (SOM). Mineral permafrost and organic (OAL) and mineral active layer (MAL) soils from Sagwon Hills, AK were analyzed for total C and N content and SOM chemical composition using Fourier transformed mid‐infrared spectroscopy (MidIR). We also investigated techniques for proper collection of MidIR spectra on high C soils, such as permafrost. Principal Components Analysis (PCA) of the MidIR spectra revealed that the OAL was different from the MAL and permafrost based on absorbance of various organic functional groups, such as hydroxyls, alkyls, carbonyls, amines, amides, and esters. The top of the permafrost (0–15 cm below the maximum active layer thaw depth) was also differentiated from the deeper permafrost (16–40 cm below) by the same organic functional groups. Spectral data suggested that there is more chemically labile C (e.g., hydroxyl, amine groups, carbohydrates) in the OAL than the top of the permafrost, which in turn has more labile C than the MAL and deeper permafrost. The chemical similarity between the top of the permafrost and the OAL, and its differences with the MAL, suggest that organic matter (OM) is introduced into the permafrost through cryoturbation. All the soils showed evidence of microbial processing, such as organic acids and carboxylates, however the relative abundance of these compounds varied by soil depth. This study advances our understanding of permafrost C chemistry and the reactivity of constituent compounds.